GROWTH OF FOUR TREE SPECIES ON MEDIA CONTAINING GOLD MINE TAILING OF PT ANTAM UBPE PONGKOR - Ulfah Juniarti Siregar; Roisatuz Zakiyah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
PT Antam UBPE Pongkor is a gold mining company that produces waste in the from of tailing mud which contains heavy metal with sufficiently high concentration. The aim of this research was to study the growth of four types of plant, i.e. Casuarina junghuniana, Pinus merkusii, Melia azedarach, and Gmelina arborea in a media containing tailing mud. This research used a completely randomized factorial design with two factors, i.e. types of plant and media. Two kinds of media was used i.e. 1200g tailing and a mixture of 900g tailing and 300g compost. Growth parameters observed were plant diameter, height, number of leaf, leaf lenght and widht, total wet and dry biomass, root-shoot-ratio and number of stomata. Soil and plant analysis was done after four months of experiment. The results showed that plant types have significant effects on all parameters except root-shoot-ratio and plant height. Media types significantly affect plant diameter, wet and dry biomass. Interaction between plant types and media gave sifnificant effect on diameter, wet and dry biomass. G. arborea had the best growth response on all parameters except root-shoot-ratio and plant heigh. Its average diameter was 4.56 mm, leaf lenght 3.67 cm, leaf widht 3.000 cm, total wet biomass 50.21 g, total dry biomass 32.19 g and number of stomata is 89.Key words: C. junghuniana, G. arborea, metal, M. azedarach, tailing, P. merkusii.